ANALISIS PERKEMBANGAN PASIEN COVID-19 MENGGUNAKAN SEGMENTASI CITRA RONTGEN TORAKS - Sumarti, Heni (JFT : Jurnal Fisika dan Terapannya, 2020)
Chest X-ray segmentation using the contour active method has been widely carried out and produces additional information for data analysis. This information can be used to determine the development of COVID-19 patients while in the hospital. The method in this study was divided into three, first taking X-ray images of patients COVID-19, second image segmentation using the active contour method then calculating area segmentation, and third calculating the deviation area in image segmentation then analyzed. The results showed that while patient in the hospital for 1-8 days 89% of patients had Â 50% decrease area clean lung, whereas only 11% of patients increased clean lung repair by about 20 - 31%. Patients who have improved this condition were hospitalized in a fairly severe condition and treated for 8 days. In general, days 1-8 patients determine at the hospital is when patients get worse showed by an decrease clean lung arean more than 50%, while days 8-14 is when the patient gets better or dies.